2018
DOI: 10.1007/s13171-018-0130-1
|View full text |Cite
|
Sign up to set email alerts
|

Procrustes Metrics on Covariance Operators and Optimal Transportation of Gaussian Processes

Abstract: Covariance operators are fundamental in functional data analysis, providing the canonical means to analyse functional variation via the celebrated Karhunen-Loève expansion. These operators may themselves be subject to variation, for instance in contexts where multiple functional populations are to be compared. Statistical techniques to analyse such variation are intimately linked with the choice of metric on covariance operators, and the intrinsic infinitedimensionality of these operators. In this paper, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 63 publications
0
48
1
Order By: Relevance
“…Specifically, Masarotto et al . () show that the Procrustes distance coincides with the Wasserstein distance between centred Gaussian processes with corresponding covariances; and, consequently, that the X il can be seen to arise hierarchically, by first generating n latent realizations ɛ il ∼ IID N (0, C ) from the ‘Fréchet mean language’ with covariance C , and then deforming them by G group‐specific operators T l , i.e. X il = T l ɛ il .…”
Section: Discussion On the Paper By Pigoli Hadjipantelis Coleman Anmentioning
confidence: 91%
See 2 more Smart Citations
“…Specifically, Masarotto et al . () show that the Procrustes distance coincides with the Wasserstein distance between centred Gaussian processes with corresponding covariances; and, consequently, that the X il can be seen to arise hierarchically, by first generating n latent realizations ɛ il ∼ IID N (0, C ) from the ‘Fréchet mean language’ with covariance C , and then deforming them by G group‐specific operators T l , i.e. X il = T l ɛ il .…”
Section: Discussion On the Paper By Pigoli Hadjipantelis Coleman Anmentioning
confidence: 91%
“…I would like to remark that this choice of geometry implicitly imposes a concrete hierarchical generative model, with an appealing interpretation in the application's context, and potential implications on the analysis, either conceptual or concrete. Specifically, Masarotto et al (2018) show that the Procrustes distance coincides with the Wasserstein distance between centred Gaussian processes with corresponding covariances; and, consequently, that the X il can be seen to arise hierarchically, by first generating n latent realizations " il ∼ IID N.0, C/ from the 'Fréchet mean language' with covariance C, and then deforming them by G group-specific operators T l , i.e. X il = T l " il .…”
Section: Adam B Kashlak (University Of Alberta Edmonton)mentioning
confidence: 92%
See 1 more Smart Citation
“…Some of the examples given on the seventh page are already Hilbertian, and the same is true for the simulations and the data analysis. The authors also mention the Procrustes metric, which has an interpretation of a Wasserstein distance in finite or infinite dimensions (Masarotto et al, 2019). Another instance of a problem combining phase variation and discrete measurements on infinite dimensional and non-linear spaces is the registration of spatial point processes ).…”
Section: Comparison Between Kernel Principal Component Analysis and Dmentioning
confidence: 99%
“…Masarotto et al (2019) observed that the Wasserstein L 2 ‐geometry is equivalent to a Procrustes‐like approach earlier proposed earlier by Dryden et al (2009), which is given by italicSPD()m0.5emchol0.5emUT*()m0.5em0.5emitalicSO()m×italicUT()m0.5em()g,aitalicga0.5emFmm+10.5em0.5emSΣmm+1. Here, the Cholesky factorization chol gives rise to a one‐to‐one map of SPD ( m ) to the full rank upper triangular matrices UT * ( m ) which embed in the upper triangular matrices UT ( m ), which map injectively into the space of centered configurations, which then project to Kendall's size‐and‐shape space.Remark (A Riemannian structure for the mildly rank deficient case) Upon close inspection, since the top dimensional stratum of SΣmk comprises all configuration matrices a with rank( a ) ≥ m − 1 (that is where SO ( m ) acts freely), with this identification, the L 2 Wasserstein space of Gaussian measures which are at most degenerate in one dimension (or of positive semi‐definite matrices rank deficient in at most one dimension) have, via the injection ), the structure of the top‐dimensional incomplete Riemannian manifold stratum of SΣmm+1, cf. Huckemann (2011a).…”
Section: Standard and Nonstandard Data Spacesmentioning
confidence: 99%